2016
DOI: 10.1016/j.chom.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Induced Spermidine-Spermine Acetyltransferase and Polyamine Depletion Restrict Zika and Chikungunya Viruses

Abstract: Polyamines are small, positively charged molecules derived from ornithine and synthesized through an intricately regulated enzymatic pathway. Within cells, they are abundant and play several roles in diverse processes. We find that polyamines are required for the life cycle of the RNA viruses chikungunya virus (CHIKV) and Zika virus (ZIKV). Depletion of spermidine and spermine via type I interferon signaling-mediated induction of spermidine/spermine N1-acetyltransferase (SAT1), a key catabolic enzyme in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
157
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(171 citation statements)
references
References 48 publications
14
157
0
Order By: Relevance
“…To determine how CHIKV may adapt to a polyamine-depleted environment, we passaged virus in BHK-21 cells that were treated with 500 μM DFMO (or left untreated for controls) for 4 days prior to infection, which we demonstrated previously to inhibit CHIKV replication but not alter cell viability or cycling (9). After each passage, viral titers were determined and used to infect the next passage at a constant multiplicity of infection (MOI) of 0.1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine how CHIKV may adapt to a polyamine-depleted environment, we passaged virus in BHK-21 cells that were treated with 500 μM DFMO (or left untreated for controls) for 4 days prior to infection, which we demonstrated previously to inhibit CHIKV replication but not alter cell viability or cycling (9). After each passage, viral titers were determined and used to infect the next passage at a constant multiplicity of infection (MOI) of 0.1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their roles within the cell, polyamines are crucial for replication of RNA viruses, including CHIKV. We previously reported that CHIKV relies on polyamines at the levels of translation and RNA-dependent RNA polymerase activity in infected cells (9). In fact, diverse RNA viruses rely on polyamines for their replication both in vitro and in vivo (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…The ODC inhibitor DL-alpha-difluoromethylornithine (DFMO) was used as a positive control for polyamine depletion in these experiments 31 . Our results reveal that the amount of polyamines in Huh7 cells is decreased under conditions of down-modulated SLC7A2 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Spermidine–spermine acetyltransferase (SAT1 or SSAT) acetylates spermidine and spermine, which promotes either their conversion back to putrescine or their export from the cell (102, 103). Interestingly, type I IFNs induce the expression of SAT1 and, therefore, deplete spermidine and spermine levels (104). The depletion of these two polyamines has a strong antiviral effect and inhibits replication of the RNA viruses, Zika virus and Chikungunya virus (104).…”
Section: Amino Acid Metabolism and Ifnsmentioning
confidence: 99%
“…Interestingly, type I IFNs induce the expression of SAT1 and, therefore, deplete spermidine and spermine levels (104). The depletion of these two polyamines has a strong antiviral effect and inhibits replication of the RNA viruses, Zika virus and Chikungunya virus (104). Mechanistically, polyamines seem to be important for transcription and translation of viral RNA and proteins.…”
Section: Amino Acid Metabolism and Ifnsmentioning
confidence: 99%